Peningkatan kualitas budidaya durian branjang melalui persilangan budidaya dan pemanfaatan limbah menjadi biogas di Desa Branjang, Kabupaten Semarang - Zaenuri, Ahmad; Witiastuti, Rini Setyo; Ranihusna, Desti; Athoillah, Athoillah; Pangastiti, Nuuferulla Kurniantyas (Penamas: Journal of Community Service, 2024)
A Durian fruit farmer in Branjang Village has difficulties cultivating durian fruit; they can also not maximize the use of durian skin waste. By collaborating with the stakeholders involved, it is possible to increase durian fruit yields through cross-cultivation techniques and managing unused durian skin waste. The Service Team has given solutions such as the need for training for durian farmers regarding durian cultivation crossbreeding techniques to have superior durian varieties, training in managing durian skin waste, which can be used as biogas, as well as collaboration with related parties such as agricultural research institutions, local and nonlocal governmental organizations to support project implementation. The method includes three activities: the selection process and training, coaching clinic group, and personal communication. The results are that durian fruit farmers produce superior varieties of durian fruit after training in crossbreeding durian cultivation. They will be able to increase sales, and durian fruit farmers will be able to process durian skin waste that has been unused into trash; after this training has finished, they can process it into biogas, which has high selling value